An integrated guidance and control approach in three-dimensional space for hypersonic missile constrained by impact angles. (January 2017) - Liu, Xiaodong; Huang, Wanwei; Du, Lifu
Abstract: A new robust three-dimensional integrated guidance and control (3D-IGC) approach is investigated for sliding-to-turn (STT) hypersonic missile, which encounters high uncertainties and strict impact angle constraints. First, a nonlinear state-space model with more generality is established facing to the design of 3D-IGC law. With regard to the as-built nonlinear system, a robust dynamic inversion control (RDIC) approach is proposed to overcome the robustness deficiency of traditional DIC, and then it is applied to construct the basic 3D-IGC law combining with backstepping method. In order to avoid the problems of "explosion of terms" and high-frequency chattering, an improved 3D-IGC law is further proposed by introducing dynamic surface control and continuous approximation approaches. From the computer simulation on a hypersonic missile, the proposed 3D-IGC law not only guarantees the stable flight, but also presents the precise control on terminal locations and impact angles. Moreover, it possesses smooth control output and strong robustness. Highlights: We explore the 3D-IGC design method for hypersonic missile which is lacking currently. A new 3D-IGC design model with more generality is deduced for hypersonic missile. A robust dynamic inversion controller is proposed to enhance the robustness of nonlinear system. A robust 3D-IGC law is proposed for hypersonic missile along with the proof of stability. The proposed 3D-IGC modeling and design method has good generality and extensionality.